A construção do vínculo afetivo no cuidado em saúde à luz da educação popular - Meira, Mateus do Amaral (2016)
This study is devoted to explicating and questioning of the theoretical and practical elements for the construction of bonding in health care, based on those of the author and other health workers experiences in the Family Health Strategy scenario (FHS), and of Popular Education in Health contributions to theoretical and methodological analysis. The construction of the bonding in the care of the relationship with the families and users of the FHS is disquieting, instigating, producing suffering and incantations in the formation of the author of this study, both as an undergraduate, set in extension experiences guided by popular education, as while health worker. Although the link is a key feature of daily services and actions in this area of the Sistema Único de Saúde (SUS), you do not see often productions that centrally look into this issue. The aim of this study was therefore to analyze the construction of affective bonds in health care from the experiences of the author and Popular Education contributions Health Therefore, we used the following methodological resources:. (1) a memorial based on the meanings of building links in professional research career; (2) participant observation, performed in order to reconstruct the experience of the researcher as an undergraduate and as a health worker, by recording in the field diary; (3) a literature search. We believe that this investigative journey contribute to the discussion about the challenges, the potential and the difficulties for the construction of bonding in health care from the local reality, centrally one where the author is inserted as a worker's Núcleo de Apoio à Família (NASF).